Strategi Pemasaran Digital untuk Meningkatkan Profitabilitas Bisnis Penjualan Sepeda Motor Second di Brejel Kidul Dawarblandong - Taufiqurrahman; Eny Setyariningsih; M Syamsul Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze and formulate an effective digital marketing strategy in increasing the profitability of the used motorcycle sales business at K-mpong Motor, Brejel Kidul, Mojokerto. The approach used is descriptive qualitative with SWOT, STP, and 7P marketing mix analysis methods. Data was collected through interviews, observations, and document analysis related to marketing activities and business operations. The results of the IFAS and EFAS analysis showed a total score of 3.31 and 3.32, respectively, which placed K-mpong Motor in Quadrant I in the SWOT matrix, so that aggressive strategy was the main choice. Internal strengths include a good local reputation and competitive selling prices, while the main weakness lies in the suboptimal use of digital media. External opportunities arise from the trend of increasing social media use and government support for MSMEs, while the threat comes from increasingly fierce competition between like-minded business actors. Recommended strategies include optimizing promotions through social media, integration with marketplace platforms, increasing digital interaction with customers, and strengthening brand image. The implementation of this strategy is expected to be able to increase sales volume and profitability in a sustainable manner, while strengthening the competitiveness of businesses in the local market. This research provides practical contributions for MSME actors in designing adaptive digital marketing strategies based on situational analysis.